The Influence of Service Quality, Price, and Promotion on Consumer Satisfaction at Ejji Coffee Dharmagiri - I Kadek Lanang Sindhu Mahendra; I Ketut Johny Pramanda Putra; A.A. Made Indra Wijaya Kusuma (PT Keberlanjutan Strategis Indonesia, 2026)
This study aims to determine and analyze the influence of service quality, price, and promotion on customer satisfaction at Ejji Coffee Dharmagiri Gianyar. The research was conducted at Ejji Coffee Dharmagiri located in Gianyar Regency, Bali, with a total sample of 98 respondents use the slovin. Data were collected through questionnaires distributed to customers, and all collected data were declared valid and reliable for analysis. Furthermore, the data were analyzed using multiple linear regression analysis and hypothesis testing, including the F-test and t-test. The results show that (1) service quality, price, and promotion simultaneously have a positive and significant effect on customer satisfaction; (2) service quality has a positive and significant effect on customer satisfaction; (3) price has a negative and insignificant effect on customer satisfaction; and (4) promotion has a positive and significant effect on customer satisfaction at Ejji Coffee Dharmagiri Gianyar.